Implementing a therapeutic intervention in pre-sport and adapted recreative activities in children with disabilities. The experience of Instituto Nacional de Rehabilitacion - Ruiz-Pingo, Roxana Leonor (2021)
We report the case of implementing an adapted sport program in children with disabilities in the Instituto Nacional de Rehabilitacion to make aware the opportunities, facilities, limitations and difficulties in its implementation. We started making guidelines of the sport program follow by its implementation.